Textbook Analysis of 'Basic English for Tourism' using Tomlinson’s Theory - Abdul Syahid; Ayu Sundari; Maulidina Tri Amanda; Rani Oktavia (Lembaga Pengembangan Kinerja Dosen, 2024)
This study analyzes the textbook